Unraveling genetic parameters for the corbicular area of Tetragonisca angustula (Hymenoptera: Apidae) - Morini, Rubia F. dos S. [UNESP] (2022)
The stingless bee, Tetragonisca angustula, known in most regions of Brazil as Jataí, is characterized as an advanced eusocial bee with a wide distribution throughout the country. This species has an ecologically and economically important role in pollination and honey production. In terms of phylogeny, it belongs to the Meliponini tribe within the corbiculate group of bees. The corbicula is a modification on the third pair of the worker bee’s legs, with a concave shape that enables the bees to store and transport pollen. The corbicular area in Apis mellifera is described as having a correlation with overall honey yield. Our aim, in this study, was to unravel the heritability traits and possible correlations related to colony health and honey production. We measured the corbicular area and body weight of 600 individuals of T. angustula from different hives and applied a Bayesian approach to estimate the genetic variance and heritability. In addition, we investigated whether or not other morphometric traits were correlated with the corbicular area. Heritability estimates were 0.56 and 0.39 for corbicular area and weight, respectively. The phenotypic correlations demonstrated a strong relationship between the corbicular area and weight, thorax and abdomen length, and also abdomen and head width. These phenotypic correlations were greater than 0.50, suggesting that the corbicular area could be a proxy trait that related to other morphometric traits such as weight. Traits like honey production and pot size should be included in further studies, unraveling the actual relation between the corbicular area and direct honey yields.